The linguistic features of texting and their utilization in a WhatsApp group of English major students - Rusfandi, R; Kurniawati, Desi; Liskinasih, Ayu (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This research investigates the linguistic features present in text messaging among students enrolled in an English literature program. The study specifically examines the WhatsApp group "Ellite Students Assemble," utilizing the classification of linguistic features developed by Ali, Hasnain, and Beg (2021) and exploring the factors that influence the use of textese. This research employs a qualitative design to analyze linguistic characteristics in digital communication, particularly on WhatsApp. The analysis encompasses morpho-syntactic and phonological features, revealing a complex phenomenon of language adaptation. A detailed examination of WhatsApp texts highlights the occurrence of each linguistic feature, providing insights into the observed patterns and tendencies. The study identifies key influences on texting styles, including informality, speed, efficiency, and creative expression. Interviews with five active participants elucidate the reasons behind their textese choices, demonstrating that individuals adjust their texting styles based on considerations of formality, efficiency, and creative expression. The results illustrate the dynamic nature of language within the WhatsApp context among English literature students. An understanding of these linguistic features and their influences offers valuable insights for educators, researchers, and language enthusiasts, contributing to a comprehensive understanding of contemporary communication practices.